Local Government Internal Audit Compliance - Greg Jones; Claire Beattie (Australasian Accounting, Business and Finance Journal, 2015)
Local government councils (LGC) rely on a number of funding sources including state and federal governments as well as their community constituents to enable them to provide a range of public services. Given the constraints on these funding sources councils need to have in place a range of strategies and policies capable of providing good governance and must appropriately discharge their financial accountabilities. To assist LGC with meeting their governance and accountability obligations they often seek guidance from their key stakeholders. For example, in the Australian State of New South Wales (NSW), the Office of Local Government has developed a set of guidelines, the Internal Audit Guidelines. In 2010 the NSW Office of Local Government issued revised guidelines emphasising that an internal audit committee is an essential component of good governance. In addition, the guidelines explained that to improve the governance and accountability of the councils, these committees should be composed of a majority of independent members. To maintain committee independence the guidelines indicated that the Mayor should not be a member of the committee. However these are only guidelines, not legislated requirements and as such compliance with the guidelines, before they were revised, has been demonstrated to be quite low (Jones & Bowrey 2013). This study, based on a review of NSW Local Government Councils’ 2012/2013 reports, including Annual Reports and associated disclosures, assesses the level of compliance with the 2010 revised guidelines, specifically in relation to internal audit committees, to determine if the guidelines are effective in improving local government council governance.
Keywords: Accountability; Audit; councils; governance; internal audit; local government